Beyond current research practice: Methodological considerations in MS rehabilitation research (is designing the perfect rehabilitation trial the Holy Grail or a Gordian knot?). (September 2019) - das Nair, Roshan; de Groot, Vincent; Freeman, Jennifer
Rehabilitation is an essential aspect of symptomatic and supportive treatment for people with multiple sclerosis (MS). The number of randomised controlled trials (RCTs) for rehabilitation interventions in MS has increased over the last two decades. The design, conduct and reporting quality of some of these trials could be improved. There are, however, some specific challenges that researchers face in conducting RCTs of rehabilitation interventions, which are often 'complex interventions'. This paper explores some of the challenges of undertaking robust clinical trials in rehabilitation. We focus on issues related to (1) participant selection and sample size, (2) interventions – the 'dose', content, active ingredients, targeting, fidelity of delivery and treatment adherence, (3) control groups and (4) outcomes – choosing the right type, number, timing of outcomes, and the importance of defining a primary outcome and clinically important difference between groups. We believe that by following internationally accepted RCT guidelines, by developing a critical mass of MS rehabilitation 'trialists' through international collaboration and by continuing to critique, challenge, and develop RCT designs, we can exploit the potential of RCTs to answer important questions related to the effectiveness of rehabilitation interventions.